Comparison of the Critical Mass Flow Rates for Two Serpentine Designs of the Photovoltaic Solar Thermal Collector - Sakhr M. Sultan; C.P. Tso; M.N. Ervina Efzan (Journal of Advanced Thermal Science Research, 2020)
A recent analysis on the photovoltaic (PV) cell efficiency for the photovoltaic solar thermal collector (PVT), cooled by forced fluid flow, revealed that there is, in general, a critical mass flow rate that corresponds to the maximum PV cell efficiency for a PVT. The derived new equations are applicable for laminar and transition or turbulent flow regimes and could yield directly the critical mass flow rate as compared with existing methods that use repeated computational trials. To demonstrate further the generality of the method, this paper reports results on comparing the critical mass flow rates for two serpentine designs with different technical details, namely Design A and Design B, using the new equations. It is shown that Design A and Design B have critical mass flow rates of 0.041 and 0.014 kg/s, respectively. The corresponding Reynolds numbers are 4078 and 2785 for Design A and Design B, respectively. It is shown that the critical mass flow rate is different from one design to another. The importance of the critical mass flow rate is summarized.